PENGARUH ELECTRONIC WORD OF MOUTH, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE THE ORIGINOTE - Puspita Sari, Tia; Ambardi, Ambardi (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
Local beauty products are growing, causing competition that makes business people try to create better and better quality products, for example, The Originote skincare products. The purpose of this study is to find out the effect of electronic word of mouth, price, and brand image partially and simultaneously on The Originote skincare product decisions. The method of this study is to use a quantitative method. The sampling technique used non-probability sampling with purposive sampling method. Data collection using a questionnaire with a sample of 113 respondents. The results showed that electronic word of mouth, price, and brand image partially and simultaneously had a significant effect on product purchasing decisions.